Novice nurses’ leadership competence: a cross-sectional study - Kalbarczyk, Agnieszka; Serafin, Lena; Czarkowska-Pączek, Bożena (Nursing in the 21st Century, 2022)
NOVICE NURSES’ LEADERSHIP COMPETENCE : A CROSS-SECTIONAL STUDY Introduction. Effective nursing leadership is a key element of the healthcare system and is essential for proper functioning and patient safety. Aim. To explore authentic leadership competencies among novice nurses and the relationship between the competencies components and sociodemographic variables. Methods. Using a descriptive cross-sectional design, data were collected in 2019 with the Authentic Leadership Self-Assessment Questionnaire – Polish adaptation (ALSAQ-P) and metrics. The analysis was based on 133 completed questionnaires. Results. The majority of novice nurses presents the average level of authentic leadership competencies. They present the low level of competence in relational self-awareness domain. The correlation of seniority with moral processing has been revealed. Compared to women, men present significantly higher authentic leadership competence. Conclusions. Novice nurses authentic leadership competencies should begin to be developed. Actions to strengthen women’s leadership competencies are also an important aspect of nursing development